To the project of architectural theory - Lidin, Konstantin (project baikal, 2023)
The existence of a general architectural theory is seriously doubted by most researchers. Based on the assumption that the modern stage of architecture development requires the construction of a workable theory, the article considers the process of creating a theory similar to the creation of an architectural project. It is shown that the axiomatic basis of the theory is similar to the foundation of a building. The complex of specific methods of analysis and synthesis in the theory is considered as an analogue of building materials and details in an architectural project. The connection of the building to infrastructure networks is analogous to the harmonisation of the approaches of the designed theory with modern general scientific concepts and paradigms. Shaping of the theory in the form of vivid visual images is similar to the design of facades with cladding and building cosmetics. It is shown that the foundation of architectural theory was laid in the late Middle Ages and retains its relevance and topicality. The other elements of the designed architectural theory need to be developed.
Keywords: architecture; theory; methodology; history; Middle Ages; modernity